A Study of 31 Patients with Primary Complaint of Halitosis in a Tertiary Hospital in South-Western Nigeria. (2019)
BACKGROUND: Halitosis is a common cause of dental consultation. Patients presenting with primary complaint of halitosis consist of dissatisfied people with genuine and pseudo-halitosis. OBJECTIVES: To assess the demographic and clinico-pathologic features of patients presenting with primary complaint of halitosis as well as evaluate the treatment outcome. METHODS: Consenting patients presenting with primary complaint of halitosis from 1st of March to 31st August, 2015 were recruited. All had intraoral examination, were screened for psychiatric morbidity and halitosis using the organoleptic method. Data concerning the complaint of halitosis was retrieved from all through an interviewer-administered structured questionnaire. All the patients were educated on the aetiology of halitosis, those with oral disease were treated and all had scaling and polishing, oral hygiene instruction/motivation in addition to hydrogen peroxide mouth rinse for two weeks. Patients’ opinions were sought concerning the presence/ intensity of halitosis at two weeks and six months post treatment. RESULTS: Thirty-one patients with a mean age of 38.48 years and male: female ratio of 1.3 were recruited. Intraoral pathology was observed in 48.4% of patients. None of the patients smoked cigarette or pipe. Twenty patients (64.5%) had been informed of the foulness of their breath by at least one person in the past; the information generated negative feelings in 19 of them. Six patients had psychiatric morbidity which was significantly associated with female gender and presence of body odour. At two weeks post treatment, 54.8% of patients were free of halitosis, while at six months only 25.8% were free. CONCLUSION: The patients who complained of halitosis were non-smokers with a mean age of 38.48±14.0 years. Intraoral pathologies were found in fifteen (15) patients, while six (6) had psychiatry morbidity. About half of the patients and about a quarter were free of halitosis following scaling and polishing and two weeks’ hydrogen peroxide mouth rinse at 2 weeks and 6 months’ reviews, respectively.